Production of cynaropicrin extracts from Cynara cardunculus leaves and its use for development of wound dressing films - Brás, Teresa Isabel de Amoreira Sousa e Silva (2020)
Natural compounds derived from plants are presently an alternative for the discovery of new effective drugs, from which new products may be developed, potentially overcoming the current limitations of synthetic compounds for use in pharma and biomedical applications. This thesis concerns the design and production of cynaropicrin enriched extracts from leaves of Cynara cardunculus, and their application in a chitosan matrix as wound dressing for antiinflammatory drug delivery. The design and production of cynaropicrin enriched extracts was performed considering the use of environmentally friendly extraction methodologies and biocompatible solvents. Selection of solvent and the extraction methodology took into consideration their effect upon cynaropicrin extraction yield, as well as energy expenditure and other operating costs. Among conventional and nonconventional extraction methodologies, ultrasound assisted extraction combined with ethanol presented the best results regarding the cynaropicrin extraction yield (55.00 mg/g Dry Weight) and energy expenditure (0.027 kWh/gcynaropicrin). Applied for the first time for cynaropicrin extraction from C. cardunculus leaves, ultrasound assisted extraction was firstly optimized regarding the pulse effect on cynaropicrin extraction yield. Comparatively to continuous mode, pulse mode (duty cycle of 25%) presented a reduction on energy consumption/gcynaropicrin, as well as a better temperature control being selected and further optimized with a response surface methodology, using the Box-Behnken design model. The results obtained confirm the applicability of the response surface methodology for optimization of cynaropicrin extraction by pulsed ultrasound assisted extraction, from C. cardunculus. Aiming the increase of the extract biological potential, fractionation of the optimized extract was performed by membrane processes. A Duramem® 200 membrane was selected for the retention of cynaropicrin while low molecular weight compounds, such as glucose and fructose, were removed by diananofiltration (after 5 diavolumes). As a result of the diananofiltration process, a global removal of 93.0% of glucose and 95.6% of fructose was obtained. An increase of the extract biological potential was achieved, when tested with a Bj5-ta human normal fibroblast cell line. The integrated process for production of cynaropicrin enriched extracts was economically assessed, leading to a pay-back period of 4.58 years, achieved for a production of 520 kg/ of extract. Incorporation of the cynaropicrin enriched extract in chitosan films, was performed by the solvent evaporation method, with different concentrations of the extract. It was shown that the extract has a negative effect on the film tensile strength and on the fluid absorption capacity being these two effects strongly influenced by the amount of extract loaded in the chitosan films. With no cytotoxic effect on Bj5-ta cell line observed, for films with an extract concentration lower to 5%, a positive effect on skin inflammation was achieved. An 86% reduction on IL-6 cytokine levels production after exposure to chitosan with 5% extract, by indirect contact, was obtained being this effect positively correlated to the cynaropicrin content in the extract loaded into the chitosan films. xii This work shows that cynaropicrin enriched extracts from C. cardunculus leaves, can be produced in a sustainable and environmentally friendly way, aiming the possibility to be scaled up for industrial applications. Besides that, its potential use as chronic skin wound dressing, allied to chitosan, is a promising approach overcoming the application of synthetic drugs, and/or potentiate their application spectrum on what regards to anti-inflammatory action.